High Density Polyethylene (HDP) Pipe as a Lining Material in Hilly Regions of Nepal - Rijal, Krishna Prasad (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
Canal lining is a major part of construction in irrigation projects. Canal lining determines the cost of project to a great extent but also the discharge delivery efficiency of the irrigation system. Though earthen canal sections are least expensive, simple to maintain and environmentally friendly, they have high seepage rates and demand frequent repair. In the light of need for resource conservation and the general unavailability of labour for maintenance work, a canal lining, though more expensive, may be justifiable in the long run. Technological advances in the construction have made available lighter and more affordable materials that enhance many parts of the irrigation process. It is the private sector that should lead the development of these technologies as they relate to the construction business. We can look to foreign markets to see how canal lining technologies have improved the use of this tool in various environments and soils. In the Nepali context, we use traditional lining techniques like stone or reinforced concrete, which are effective in the plains, but less so in the hills and remote. In this paper, I review some alternatives to traditional canal linings, and examine the virtues of high density polyethylene (HDP) pipe for possible use in irrigation schemes. HYDRO Nepal Journal of Water Energy and Environment Volume- 18, 2016, January Page -25-29